Understanding the care.data conundrum: new information flows for economic growth - Vezyridis, Paraskevas; Timmons, Stephen (Sage, 2017)
The analysis of data from electronic health records aspires to facilitate healthcare efficiencies and biomedical innovation. There are also ethical, legal and social implications from the handling of sensitive patient information. The paper explores the concerns, expectations and implications of the National Health Service (NHS) England care.data programme: a national data sharing initiative of linked electronic health records for healthcare and other research purposes. Using Nissenbaum’s contextual integrity of privacy framework through a critical science and technology studies (STS) lens, it examines the way technologies and policies are developed to promote sustainability, governance and economic growth as the de facto social values, while reducing privacy to an individualistic preference. The state, acting as a new, central data broker reappropriates public ownership rights and establishes those information flows and transmission principles that facilitate the assetisation of NHS datasets for the knowledge economy. Various actors and processes from other contexts attempt to erode the public healthcare sector and privilege new information recipients. However, such data sharing initiatives in healthcare will be resisted if we continue to focus only on the monetary and scientific values of these datasets and keep ignoring their equally important social and ethical values.